Differential responses of a pi-class glutathione S-transferase (CnGSTp) expression and antioxidant status between golden and brown noble scallops under pathogenic stress. Issue 105 (October 2020) - Liu, Hongxing; Zhang, Hongkuan; Cheng, Dewei; Tan, Karsoon; Ye, Ting; Ma, Hongyu; Li, Shengkang; Zheng, Huaiping
Abstract: Glutathione S-transferases (GSTs) play important roles in immunity by protecting organisms against the damage of reactive oxygen species (ROS). In this study, a pi-class GST cDNA sequence was first cloned from noble scallop Chlamys nobilis (named CnGSTp ). The full length cDNA of CnGSTp was 922 bp, encoding a cytosolic protein of 202 amino acids residues, with predicted molecular masses of 23.1 kDa. Then an acute Vibrio Parahaemolyticus challenge experiment was conducted by using the Golden and Brown noble scallops with different total carotenoids content (TCC), and CnGSTp expression level, TCC and ROS level was separately determined. The results showed that ROS and CnGSTp expression levels were significantly up-regulate under Vibrio Parahaemolyticus challenge than the control group ( P  < 0.05). The Golden scallops showed significantly higher CnGSTp expression level and lower ROS level in hemocytes than the Brown ones ( P  < 0.05). Moreover, there is a significantly positive correlation between TCC and ROS in the Golden scallops. The present results revealed that CnGSTp plays important roles in immune response and carotenoids play assistant roles in antioxidant defense system under pathogenic stress in the noble scallop. Highlights: CnGSTp was identified and played important roles in immune response in the noble scallop. Differential responses of CnGSTp gene and ROS level exist between Golden and Brown scallops. Carotenoids can play antioxidant role by decreasing ROS level in the scallops' hemocytes.